Nox-2-mediated phenotype loss of hippocampal parvalbumin interneurons might contribute to postoperative cognitive decline in aging mice - qiu, lili; luo, dan; zhang, hui; shi, yun s.; li, yanjun; wu, dan; chen, jiang; ji, muhuo; Yang, Jianjun (Frontiers in Aging Neuroscience, 2016)
Postoperative cognitive decline (POCD) is a common complication following anesthesia and surgery, especially in elderly patients; however, the precise mechanisms of POCD remain unclear. Here, we investigated whether nicotinamide adenine dinucleotide phosphate (NADPH) oxidase mediated-abnormalities in parvalbumin (PV) interneurons play an important role in the pathophysiology of POCD. The animal model was established using isoflurane anesthesia and exploratory laparotomy in sixteen-month-old male C57BL/6 mice. For interventional experiments, mice were chronically treated with the NADPH oxidase inhibitor apocynin (APO). Open field and fear conditioning behavioral tests were performed on day 6 and 7 post-surgery, respectively. In a separate experiment, brain tissue was harvested and subjected to biochemical analysis. Primary hippocampal neurons challenged with lipopolysaccharide in vitro were used to investigate the mechanisms underlying the oxidative stress-induced abnormalities in PV interneurons. Our results showed that anesthesia and surgery induced significant hippocampus-dependent memory impairment, which was accompanied by PV interneuron phenotype loss and increased expression of interleukin-1β, markers of oxidative stress, and NADPH oxidase 2 (Nox2) in the hippocampus. In addition, lipopolysaccharide exposure increased Nox2 level and decreased the expression of PV and the number of excitatory synapses onto PV interneurons in the primary hippocampal neurons. Notably, treatment with APO reversed these abnormalities. Our study suggests that Nox2-derived ROS production triggers, at least in part, anesthesia- and surgery-induced hippocampal PV interneuron phenotype loss and consequent cognitive impairment in aging mice.